EVALUATION OF THE POTENTIAL APPLICATION OF LOW DENSITY POLYETHYLENE PLASTIC WASTE TREATMENT BY MARINE MICROORGANISMS IN THE COASTAL AREA OF BA RIA-VUNG TAU PROVINCE, VIETNAM - Thi Thu Hong Do; Thi Thu Trang Dinh; Thanh Xuan Phan; Trong Nguyen Trinh; Phuoc Thien Hoang Truong; Van Nam Thai (HUIT Journal of Science, 2025)
Low density polyethylene (LDPE) plastic waste is a type of non-degradable solid waste that poses a significant threat to the environment globally. Among various degradation methods, biodegradation, which involves microorganisms, is the most efficient and sustainable solution. It stands out for its environmentally friendly process, lack of pollution, and cost-effectiveness. This study evaluates the potential application in the treatment of low density polyethylene plastic waste by marine microbiology isolated from the sea of Ba Ria - Vung Tau province, Vietnam. From 12 samples (09 marine sediment samples and 03 plastic waste samples), 27 microbial strains were selected through enrichment with 0.5% LDPE substrate. In which, marine sediment samples recorded a higher ratio of strains per sample than plastic waste samples. Based on the ability to produce laccase enzyme, 12 strains (with laccase enzyme activity from 750.0 ± 3.00 U/mL to 1430.0±3.66 U/mL) were selected for identification and study of antagonism between strains. There were 03 microbial formulas formed including: microbial formula 1 (MF1) including strains: S1.05, S3.01, S3.03, S4.01; microbial formula 2 (MF2) including strains: S2.02, S6.01, S6.03, S8.01; microbial formula 3 (MF3) includes strains: S9.04, S10.01, S11.01, S11.02. The three microbial formulas were cultured in mineral medium supplemented with 0.5 % LDPE substrate. MF3 is the microbial formula with the best ability to reduce substrate weight (reduced by 17.4% compared to the initial substrate amount after 90 days of culture). Microbial formula MF3 has the potential to be applied to create microbial preparations for treating plastic waste originating from LDPE. The results obtained from this study can be a reliable source of data for the research and development of a microbial preparation for treating plastic waste, contributing to solving the current plastic waste pollution situation.